3(x-3)+6=4(x+3)

Simple and best practice solution for 3(x-3)+6=4(x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-3)+6=4(x+3) equation:


Simplifying
3(x + -3) + 6 = 4(x + 3)

Reorder the terms:
3(-3 + x) + 6 = 4(x + 3)
(-3 * 3 + x * 3) + 6 = 4(x + 3)
(-9 + 3x) + 6 = 4(x + 3)

Reorder the terms:
-9 + 6 + 3x = 4(x + 3)

Combine like terms: -9 + 6 = -3
-3 + 3x = 4(x + 3)

Reorder the terms:
-3 + 3x = 4(3 + x)
-3 + 3x = (3 * 4 + x * 4)
-3 + 3x = (12 + 4x)

Solving
-3 + 3x = 12 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-3 + 3x + -4x = 12 + 4x + -4x

Combine like terms: 3x + -4x = -1x
-3 + -1x = 12 + 4x + -4x

Combine like terms: 4x + -4x = 0
-3 + -1x = 12 + 0
-3 + -1x = 12

Add '3' to each side of the equation.
-3 + 3 + -1x = 12 + 3

Combine like terms: -3 + 3 = 0
0 + -1x = 12 + 3
-1x = 12 + 3

Combine like terms: 12 + 3 = 15
-1x = 15

Divide each side by '-1'.
x = -15

Simplifying
x = -15

See similar equations:

| 3k+8=68 | | (2x+9)(x-4)=0 | | 4x+4(6x+7)=168 | | -3x-8y=16 | | 2y^2-5y^2=7 | | x-.25x=20.25 | | -3x+8y=16 | | -5v-6=3v+19 | | 0=2x^2-20x+57 | | (1/b)=(-3)/(b+2) | | 8b^3/10b | | 12a/4a^2 | | -5x+3y+1=0 | | S=2ab+2ac | | 12a/4a^28b^3/10b | | -3=6(f-5) | | 12/7=27/14a | | 6x-3(x-8)=4(x-7)+6 | | x^4-9x-3=0 | | 16x-19=133-6 | | 4x-(m+10)=60 | | -9(-4)+7=25+2 | | 2(a+6)=22 | | 63/(x+2) | | -38/3=10/9y | | 4x^2-3x+11=9x+6 | | 5(2x+3)-2(x-4)=2x-1 | | 2(x+2)(x-4)4=0 | | -34=42+-4v | | (X+3)(X+4)(X+5)=0 | | (X-3)(Y+7)=0 | | 6(5-2y)-5(y+3)= |

Equations solver categories